Diversity of Mollusca, Arthropods, and Pisces in the Estuarine Areas of Gampong Jawa and Gampong Alue Naga as Implications for the Community Economy - Ibrahim; Aiza Rafsanjani; Jalaluddin Jalaluddin; Azwir; Dian Aswita; Nurlena Andalia (Postgraduate, University of Mataram, 2025)
This study aims to analyze the distribution of species on three different transects to evaluate the diversity of aquatic ecosystems and its implications for the economic potential of coastal communities. Sampling methods were carried out on three transects by recording the abundance of 48 species from the mollusk, crustacean, and fish groups. Data analysis included the calculation of the Shannon-Wiener diversity index (H), evenness index (J), and dominance index (C). The results showed that Transect B had the highest total abundance (2,617 individuals) with the highest diversity index (H=2.617) and the best evenness (J=1.094). Dominant species differed on each transect, with Setipinna taty dominating Transect A (500 individuals), Petek (Secutor rocunius) dominant in Transect B (500 individuals) and Transect C (450 individuals). Species distribution showed significant habitat heterogeneity with some species showing specific habitat preferences. From an economic perspective, the presence of high-value commercial species such as kalampa anchovies, green mussels, mangrove crabs, and tiger prawns demonstrates significant potential for the development of capture fisheries, aquaculture, seafood processing, and marine ecotourism. High species diversity opens up opportunities for business diversification that can reduce economic risks and increase incomes in coastal communities. This study recommends sustainable management that integrates conservation with economic development through zoning of water use, establishing sustainable fishing quotas, and developing community capacity in seafood processing.